Analysis of Foreign Direct investment in West Africa - Hassan, David Vincent; Aneikan, Akpansung (Journal of Quantitative Methods, 2025)
This study examined the impact of foreign direct investment (FDI) on economic growth in West African countries. The findings highlight that FDI and gross fixed capital formation are key drivers of economic growth in the region. While most West African nations experience a positive relationship between FDI and economic growth, some countries exhibit a negative correlation. The analysis also indicates that high exchange rates and inflation levels hinder economic growth. Moreover, the significance of the constant term in the model underscores the vital role FDI plays in boosting economic performance across the region. Based on these findings, the study recommends that governments implement policies aimed at increasing FDI inflows. These could include measures such as tax holidays, the establishment of free trade zones, and other incentives designed to attract foreign investors. Additionally, efforts should be made to reform exchange rate policies to ensure stability and competitiveness. Controlling inflation should also be a priority, and central banks are encouraged to adopt strategies that reduce inflation to single-digit levels. Let me know if you need this formatted for a conclusion section or turned into bullet points for a presentation.